การตรัสรู้ของพระพุทธเจ้า - นีละโยธิน, อัครเดช (วารสารวิชาการพระพุทธศาสนาเขตลุ่มน้ำโขง; Vol 1 No 2 (2018): ปีที่ 1 ฉบับที่ 2 ประจำเดือนกรกฎาคม - ธันวาคม 2561, 2018)
The enlightenment by himself of the Lord Buddha is the supreme dhamma phenomenon, the dhamma truth which is the natural law of the universe. that everyone and everything must be under this rule. Therefore, the dharma which had discovered by the Lord Buddha is timeless and cause Buddhism different from other religions and being the universal religion of the world. This is also a good sign of human independence to escape from round of rebirth. when the Lord Buddha showed those truths and he explained how to release from suffering. whom who aim to escape from suffering could hold and practice on the guidelines of the Lord Buddha and they could be able to release from all of suffering and achieve the enlightenment equally. The way to escape from that suffering, the Buddha had shown in many ways but the shortest way is to follow the noble eightfold paths which means the training in higher of morality mentality and wisdom. As long as humans continue to practice on the way of the Lord Buddha, then Buddhism will not deteriorate from this world. Keywords: Enlightenment, Buddha.